PERANAN SEKTOR DAN SUBSEKTOR INDUSTRI PENGOLAHAN 2000 DALAM PEREKONOMIAN JAWA BARAT -2010: PENDEKATAN INPUT OUTPUT - , YUSUF RIYANTO; , Prof. Dr. Samsubar Saleh, M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Many regions or countries believed that the manufacturing sector has a role as a leading sector for the economy to grow through the nature of the linkage of manufacturing sector both backward and forward. During 2000-2012, West Java has contributed to Indonesian GDP by an average of 14.4 percent. During 1993- 2011, manufacturing sector accounted for 39 percent of West Java GDP. However, the high contribution of the manufacturing sector make economic growth in West Java more vulnerable to the global economic crisis compared to the average national economic growth. This study aims to analyze the role of manufacturing in the economy of West Java in 2000-2010, with the indicators are the structure of output, gross value added, demand, export-import, multiplier, and the linkages between sectors